Combinatorial Effects of Ursodeoxycholic Acid and Antibiotic in Combating Staphylococcus aureus Biofilm: The Roles of ROS and Virulence Factors - Anuradha Tyagi; Vinay Kumar; Navneet Joshi; Harish Kumar Dhingra (Microorganisms, 2024)
Staphylococcus aureus is a biofilm-forming bacterium responsible for various human infections, one particularly challenging to treat due to its antibiotic resistance. Biofilms can form on both soft tissues and medical devices, leading to persistent and hard-to-treat infections. Combining multiple antimicrobials is a potential approach to overcoming this resistance. This study explored the effects of ursodeoxycholic acid (UDCA) combined with the antibiotic ciprofloxacin against S. aureus biofilms, aiming to evaluate any synergistic effects. Results showed that UDCA and ciprofloxacin co-treatment significantly reduced biofilm formation and disrupted pre-formed biofilms more effectively than either agent alone (p < 0.01). The combination also displayed a slight synergistic effect, with a fractional inhibitory concentration of 0.65. Additionally, the treatment reduced the production of extracellular polymeric substances, increased reactive oxygen species production, decreased metabolic activity, altered cell membrane permeability, and lowered cell surface hydrophobicity in S. aureus. Furthermore, it diminished biofilm-associated pathogenic factors, including proteolytic activity and staphyloxanthin production. Overall, the UDCA–ciprofloxacin combination shows considerable promise as a strategy to combat infections related to staphylococcal biofilms, offering a potential solution to the healthcare challenges posed by antibiotic-resistant S. aureus.